A Comparative Study of Serum Thyroxine, Tri-Iodothyronine and Thyrotropin Between Low Birth Weight and Normal Birth Weight Neonate - M A Matin; Ahmed, Md Sultanuddin; T Rahman (Journal of Dhaka National Medical College & Hospital, 2016)
This was a prospective randomized study. The period of study was from April 2005 to May 2006 and conducted in the department of Pediatrics and obstetrics in BSMMU, in DMCH and in the Institute of nuclear Medicine (INM). A total of 90 neonates of either sex of postnatal age ranging from 3-6 days were selected for this study. They were divided into three groups of 30 preterm LBW (gestational age < 37weeks & birth weight <2.5 kg) neonates, 30 full-term small for gestational (SGA) age (gestational age ≥ 37weeks & birth weight < 2.5 kg) and 30 full-term appropriate for gestational (AGA) age (gestational age ≥ 37weeks & birth weight ≥ 2.5 kg) neonates. The mean of gestational age of preterm LBW, full term SGA and full term AGA were 34.73 ± 0.20 weeks, 38.6 ± 0.21 weeks and 38.80 ± 0.15 weeks respectively. We studied their thyroid function status by estimating serum T3, T4 and their controlling homone TSH and then the results were compared between the groups. We observed that the mean serum T3 & T, level in low birth weight neonates were significantly lower in comparison to those of the full term AGA neonates. The estimated mean values of serum T3, T4 levels were lowest in preterm LBW neonates-(T, =0.93 ± 0.05 nmol/1 and T4 129.29± 6.33 nmol/1), highest in full-term AGA neonates (T3 = 1.98 ± 0.05 nmol/1 and T4 188.47 ± 3.66 nmol/l) and intermediate in full term SGA neonates (T3=1.49 ± 0.03 nmol/l and T4= 152.66 ± 2.87 nmol/l). Regarding TSH value there was no significant difference between the groups (TSH in preterm LBW 6.52 ±0.46 miu/l, in full term SGA 6.37 ±0.30 miu/l, full term AGA 5.69± 0.35 miu/l).There were positive correlation (r) found between T, & T4 with birth weight and gestational age and negative correlation between TSH and birth weight and no correlation with gestational age. It found that higher the birth weight higher was the value of serum T, and T, but TSH level did not differ. From our study as serum T, and T, levels were lower in LBW neonates than that of the full term (AGA) and TSH level did not vary between groups So we concluded that during thyroid screening program both T, and TSH are considered. On the basis of our findings we recommended that in preterm LBW or in low birth weight neonates where serum T, level is at hypothyroid level (<64.5nmol/l) with normal TSH should be kept under regular follow up till T, value become normal J. Dhaka National Med. Coll. Hos. 2016; 22 (02): 36-40